A method for revealing and mounting white arisaema juice paste painting based on borax-white arisaema polysaccharide complexing and viscosity transfer

CN122939262APending Publication Date: 2026-10-20ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611163247.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,对于含白芨汁的糨糊,该方法存在以下根本性缺陷:(1)分离机制缺陷:对于难揭展的纸质书画,用水揭展时,由于白芨糨糊的强氢键网络,浆糊分别将画心和命纸的半层粘结成为一体无法分开,揭展的实际分离层是从画心的半层或从命纸的半层分开,造成纸张纤维的不可逆损伤;(2)效率低下:一幅作品需2小时以上,且成功率低,高度依赖修复师个人经验;(3)机械损伤风险:手工搓捻过程中,剪切力易超过纸张纤维的抗拉强度,导致纤维断裂、纸张分层

Benefits of technology

[0044](1)解决了“糊有白芨者尤难”的难题:本发明通过硼砂与白芨多糖顺式邻二羟基的选择性络合,首次实现了对白芨多糖网络的特异性弱化,从根本上解决了这一困扰书画修复界数百年的技术瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a method for removing and mounting calligraphy and paintings using Bletilla striata juice paste based on borax-Bletilla striata polysaccharide complexation and adhesive transfer, comprising: (a) interface pretreatment: applying a pretreatment aqueous solution containing borax, urea, and glycerol to the back of the painting core, and covering it with a thin film for moisturizing; (b) adhesive transfer: removing the covering film and attaching the adhesive transfer film to the treated area; (c) controlled peeling: peeling off the adhesive transfer film under the application of counterweight, so that the adhesive substances in the calligraphy and painting adhesive layer are transferred to the adhesive transfer film, realizing the separation of the painting core from the backing paper; (d) interface cleaning: checking the interface, repeating steps (b) and (c) until the backing paper can be separated without resistance, and finally cleaning the residual impurities. This invention selectively weakens the BSP network through molecular recognition and achieves controlled peeling by physical adhesive transfer, which can solve the technical problem of the "especially difficult" removal of paste containing Bletilla striata juice, thereby achieving non-destructive, controllable, and efficient restoration of fragile paper cultural relics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of paper cultural relic protection and restoration technology, specifically involving a method for mounting and unmounting calligraphy and paintings using Bletilla striata juice paste based on borax-Bletilla striata polysaccharide complexation and viscosity transfer. Background Technology

[0002] Chinese calligraphy and painting mounting techniques have a long history of over 1,700 years. As the core adhesive material in mounting, the preparation and application of paste directly determine the durability and reversibility of the mounted artwork. In traditional high-end mounting techniques, juice from Bletilla striata tubers is often added to starch-based paste, utilizing the excellent adhesive properties of Bletilla striata polysaccharides to enhance the paste's bonding strength and flexibility.

[0003] Bletilla striata is a perennial herbaceous plant of the Orchidaceae family. Its tubers are rich in BSP, a polysaccharide composed of mannose (Man) and glucose (Glc) main chains linked by β-1,4-glycosidic bonds in a molar ratio of approximately 4:1. It also contains α-L-arabinofuranose (Araf) and α-D-glucuronic acid (GlcA) side chains, with a weight-average molecular weight (Mw) of 280,000-722,900 Da. The BSP molecular chain is rich in hydroxyl groups (-OH), which form a three-dimensional network structure with starch molecules through hydrogen bonding, giving the paste layer the following characteristics: (1) High bonding strength: BSP forms multiple hydrogen bonds and physical entanglement with paper cellulose fibers, resulting in durable adhesion; (2) Flexibility: The linear long-chain structure of BSP gives the paste layer good mechanical flexibility; (3) Anti-aging properties: The β-1,4-glycosidic bonds of BSP are more resistant to hydrolysis than the α-1,4-glycosidic bonds of starch. However, it is precisely these excellent properties that make it extremely difficult to remove aged Bletilla striata paste. Zhou Jiaju of the Ming Dynasty clearly pointed out in his "Treatise on Removal of Bletilla striata Paste" that "paste with Bletilla striata paste is especially difficult to remove," and this problem continues to this day, becoming a technical bottleneck in the field of calligraphy and painting restoration.

[0004] Traditional mounting and unmounting methods mainly involve wetting the paper with water and then manually rubbing it. The principle is to use water penetration to make the paste layer swell and soften, reducing its bonding strength, and then use mechanical force to separate the backing paper from the painting. However, for paste containing Bletilla striata juice, this method has the following fundamental defects: (1) Defects in the separation mechanism: For paper paintings and calligraphy that are difficult to unmount, when using water to unmount them, due to the strong hydrogen bond network of Bletilla striata paste, the paste will bond the painting and the backing paper half-layers together and cannot be separated. The actual separation layer is from the half-layer of the painting or the half-layer of the backing paper, causing irreversible damage to the paper fibers; (2) Low efficiency: It takes more than 2 hours to mount a work, and the success rate is low, which is highly dependent on the personal experience of the restorer; (3) Risk of mechanical damage: During the manual rubbing process, the shearing force is easy to exceed the tensile strength of the paper fibers, resulting in fiber breakage and paper delamination.

[0005] In 2015, the Capital Museum unveiled a technique for revealing ancient paintings and calligraphy using the extracellular fluid of Bacillus subtilis. This technique utilizes α-amylase in the bacterial solution to decompose starch binders, reducing the peeling force from approximately 35 mN in traditional methods to 13 mN, increasing efficiency by more than a hundred times. However, this technique has the following inherent limitations: (1) Insufficient specificity: Amylase can only hydrolyze the α-1,4-glycosidic bonds of starch, and has almost no effect on the β-1,4-glycosidic bonds of Bletilla striata polysaccharide. For paste containing Bletilla striata juice, enzymatic methods cannot effectively degrade the BSP network, greatly reducing the peeling effect and failing to solve the core problem of "paste containing Bletilla striata is particularly difficult to peel"; (2) Risk of protein residue: biological enzyme preparations are essentially proteins. Even after washing, there may still be trace amounts of residue in the cultural relics, which can become a source of nutrients for microorganisms, leading to mold and biodegradation risks; (3) Complex process control: enzyme activity is significantly affected by temperature (optimal 35-40℃) and pH (optimal 6.0-7.0). Strict control of the action conditions is required, and the operation tolerance is low. Excessive action may lead to excessive decomposition of the paste, affecting the integrity of the paper; (4) Limited applicability: for heavy color paintings, prolonged soaking (usually more than 30 minutes) may still cause the pigment layer to bleed or fall off.

[0006] In addition, some restoration institutions have also tried to soften the paste using organic solvents (such as ethanol, acetone, ethyl acetate) or chemical reagents (such as urea solution, surfactants). However, these methods have the following problems: (1) Safety risks: Organic solvents are flammable and explosive, which are harmful to operators and the environment; (2) Residue problems: Chemical reagents may remain in the paper fibers, which will affect the stability of cultural relics in the long term; (3) Side effects: Strongly polar solvents may cause paper deacidification, excessive fiber swelling, or discoloration and peeling of the pigment layer.

[0007] It is worth noting that although borax has been used in the field of paper deacidification and buffering, there has long been a technical bias in the field of calligraphy and painting restoration that "chemical reagents inevitably damage cultural relics." Moreover, in the practice of cultural relic protection, borax is only recognized as a pH adjuster and has never been used for the selective weakening of the paste layer. The existence of this technical bias means that even those skilled in the art with basic chemical knowledge lack the motivation to apply the borax-polysaccharide complexation principle to the process of unmounting calligraphy and paintings.

[0008] Based on the analysis of the above-mentioned existing technologies, there is an urgent need in this field for a method of removing and mounting calligraphy and paintings using Bletilla striata polysaccharide as paste: (1) specifically acts on Bletilla striata polysaccharide, solving the technical problem of "paste with Bletilla striata is especially difficult"; (2) no biological or chemical residues, avoiding long-term potential harm to cultural relics; (3) the process is highly controllable and adaptable to calligraphy and paintings of different aging degrees and fragility; (4) the operation is simple and does not require complex equipment or harsh conditions; (5) the separation is thorough and non-destructive, realizing the complete separation of the painting core and the mounting paper. Summary of the Invention

[0009] The purpose of this invention is to provide a method for removing and mounting calligraphy and paintings using Bletilla striata juice paste based on borax-Bletilla striata polysaccharide complexation and viscous transfer. This invention selectively weakens the BSP network through molecular recognition and achieves controllable peeling through physical viscous transfer, thus solving the technical problem of the "especially difficult" removal of paste containing Bletilla striata juice, and realizing non-destructive, controllable, and efficient restoration of fragile paper cultural relics.

[0010] The technical solution of the present invention is as follows: A method for mounting and unmounting calligraphy and paintings using Bletilla striata juice paste based on borax-Bletilla striata polysaccharide complexation and viscosity transfer, comprising the following steps:

[0011] (a) Interface pretreatment: Taking Bletilla striata juice paste calligraphy and painting as the object, a pretreatment aqueous solution containing 1-3wt% borax, 0.1-0.3mol / L urea and 5-10vol% glycerol was applied to the back of the painting core. The painting was then covered with a plastic film for moisture retention treatment, so that borax ions and the cis-hydroxyl groups of Bletilla striata polysaccharide (BSP) formed a reversible complex, which changed the hydration state and rheology of the paste layer and weakened the hydrogen bond network density between BSP molecules. Urea, as a hydrogen bond competitive disruptor, synergistically reduced the hydrogen bond network density between BSP molecules.

[0012] (b) Adhesive transfer: Remove the covering film and attach the adhesive transfer film to the treatment area; the adhesive transfer film is made of 1-3 wt% sodium alginate, 1-3 wt% gelatin, 5-15 wt% glycerol, and water, and is treated with calcium ion crosslinking.

[0013] During the calcium ion crosslinking process, sodium alginate and gelatin form an interpenetrating network of "egg box" structural domains and gelatin triple helix structure through calcium ion crosslinking.

[0014] The viscous transfer membrane of this invention has a three-layer structure: the surface layer is a sodium alginate-rich region with high adhesion; the middle layer is a sodium alginate / gelatin interpenetrating network (IPN) providing moderate cohesive strength; and the bottom layer is a high cross-linking density support layer. This viscous transfer membrane is a polysaccharide-protein composite hydrogel membrane with a higher affinity to Bletilla striata juice paste and a higher cohesion ratio (adhesion / cohesion ratio > 1.5). It exhibits preferential adhesion to aged paste, maintains tack for 2-4 hours, and demonstrates greater adhesion work to BSP than to Xuan paper fibers.

[0015] (c) Controlled peeling: at 2-4 g / cm 2 By applying a counterweight to the surface density of the loaded surface, the adhesive transfer film is slowly peeled off, so that the adhesive material in the painting and calligraphy adhesive layer is transferred to the adhesive transfer film, thereby achieving the separation of the painting core and the backing paper.

[0016] (d) Interface cleaning: Check the interface and repeat steps (b) and (c) until the paper can be separated without resistance. Finally, clean the remaining impurities with a moist cotton swab.

[0017] This invention selectively weakens the BSP network through molecular recognition and achieves controllable peeling using physical adhesive transfer. It solves the technical challenge of removing paste containing Bletilla striata juice, making it particularly difficult, and enables non-destructive, controllable, and efficient restoration of fragile paper artifacts. Specifically:

[0018] The borax-Bletilla striata polysaccharide complexation mechanism of this invention is as follows: Borax (Na2B4O7·10H2O) hydrolyzes in water:

[0019] B4O7 2- +7H₂O→4B(OH)₃+2OH⁻ -

[0020] B(OH)3 + H2O → B(OH)4 - +H +

[0021] Tetrahydroxyborate [B(OH)4] - It has an empty p orbital and can form a stable five-membered cyclic borate ester complex with the cis-diol on the BSP molecular chain. The above complexation reaction has the following characteristics: (1) Reversibility: equilibrium constant K≈10 3 L / mol, which can be reversed by dilution or the addition of competitive polyols (such as glycerol); (2) Selectivity: It only reacts with cis dihydroxyl and has no effect on trans dihydroxyl of cellulose, thus protecting paper fibers; (3) Structural damage: After complexation, the hydration layer of BSP molecular chains thickens, hydrogen bond donors decrease, and network viscosity decreases significantly.

[0022] The design principle of the boron adhesive transfer membrane of this invention is as follows: The adhesive transfer membrane adopts sodium alginate / gelatin composite hydrogel, based on the following design: (1) Adhesion selectivity: Sodium alginate is a polyanionic polysaccharide, which has molecular similarity with aged BSP (containing glucuronic acid side chain), and preferentially adheres through hydrogen bonds and van der Waals forces; (2) Cohesive strength regulation: through Ca 2+ Cross-linked sodium alginate forms an “egg box” structure, gelatin forms a triple helix structure, and an interpenetrating network (IPN) is constructed with moderate cohesive strength; (3) Adhesion optimization: Adhesion lasts for 2-4 hours to ensure sufficient adhesion but not excessive penetration.

[0023] In summary, the core of this invention lies in the synergistic combination of the following technical features: (1) Borax concentration 1-3wt%: less than 1% is insufficient for complexation, and more than 3% may penetrate into the pigment layer; (2) Glycerol 5-10vol%: moisturizes and participates in competitive complexation, controlling the reaction rate; (3) Urea 0.1-0.3mol / L: hydrogen bond competitor, synergistically reducing the density of the BSP network; (4) Adhesive transfer film moisture content 60-80%: balances adhesion and cohesive strength.

[0024] Preferably, in step (a), the molar ratio of urea to borax is 1:5 to 1:15.

[0025] Preferably, in step (a), the moisturizing treatment time is 60-120 minutes.

[0026] Preferably, in step (a), the amount of the pretreatment aqueous solution used is 0.1-1 mL / cm³. 2 .

[0027] Preferably, in step (b), the method for preparing the viscous transfer film includes:

[0028] (1) Soak the gelatin in a water bath;

[0029] (2) Add sodium alginate and glycerol, and stir until completely dissolved;

[0030] (3) Vacuum degassing;

[0031] (4) Cast onto a release film and immediately spray with CaCl2 solution for crosslinking treatment;

[0032] (5) Static equilibration treatment to form a gel-like viscous transfer membrane with a water content of 60-80wt%.

[0033] Sodium alginate has a viscosity of 200-500 mPa·s in a 1% aqueous solution at 25°C; gelatin has a Bloom strength of 150-250 g. The two are cross-linked by calcium ions to form an interpenetrating network of "egg-box" structural domains and a gelatin triple helix structure. The viscous transfer film prepared by the above method of this invention has a three-layer structure: the surface layer is a sodium alginate-rich region with high adhesion; the middle layer is a sodium alginate / gelatin interpenetrating network (IPN) providing moderate cohesive strength; and the bottom layer is a high-crosslink density support layer. The viscous transfer film of this invention exhibits preferential adhesion to aged paste, with a holding time of 2-4 hours, and its adhesion work to BSP is greater than its adhesion work to Xuan paper fibers.

[0034] Preferably, in step (1), the temperature of the water bath is 50-70°C and the swelling time is 20-40 minutes.

[0035] Preferably, in step (2), the stirring temperature is 50-70℃ and the stirring time is 1-3 hours.

[0036] Preferably, in step (3), the vacuum degassing pressure is -0.1 MPa and the time is 20-40 minutes.

[0037] Preferably, in step (4), the concentration of the CaCl2 solution is 0.05-0.2M and the crosslinking time is 20-40 seconds.

[0038] Preferably, in step (5), the conditions for the static equilibration treatment are: 20-30℃, relative humidity 60-70%, and equilibration time 20-30 hours.

[0039] Preferably, in step (c), the counterweight is held for 30-60 minutes.

[0040] Preferably, in step (c), the viscous transfer film is slowly peeled off at an angle of 10-30°.

[0041] By optimizing the transmission of peeling force, damage to calligraphy and paintings during shearing can be avoided.

[0042] Preferably, in step (d), residual impurities are finally cleaned with a moistened cotton swab.

[0043] Compared with the prior art, the present invention has the following significant advantages:

[0044] (1) Solved the problem of "especially difficult to paste with Bletilla striata": This invention achieves the first specific weakening of the Bletilla striata polysaccharide network by selectively complexing borax with the cis-ortho-dihydroxy group of Bletilla striata polysaccharide, fundamentally solving this technical bottleneck that has plagued the calligraphy and painting restoration industry for hundreds of years.

[0045] (2) Achieving non-destructive remounting: This invention utilizes a synergistic mechanism of "borax complexation + adhesive transfer" to ensure that the fracture surface during the peeling process occurs at the interface between the painting core and the glue layer, with the glue layer being transferred entirely to the adhesive transfer film. SEM observation shows that after remounting, the fibers on the back of the painting core are loosely arranged, the surface is smooth and clean, there is no obvious glue residue, the fiber morphology is intact, and no crushing or breakage marks are observed, thus achieving truly non-destructive remounting.

[0046] (3) No biological or chemical residues: This invention does not use any biological enzyme preparations (risk of protein residues) or harmful organic solvents. It uses small molecule compounds such as borax, urea, and glycerol and natural polysaccharide / protein materials throughout the process, which are easy to clean and have no long-term potential harm to cultural relics.

[0047] (4) Controllable process and simple operation: This invention does not require strict control of temperature, pH and other conditions, and does not require complicated equipment. Repair personnel can complete the operation under normal conditions, which greatly reduces the technical threshold and failure risk of unmounting and mounting, and is conducive to the promotion and application of the technology.

[0048] (5) Wide applicability: By adjusting the borax concentration (1-3wt%) and treatment time (60-120 minutes), the method of the present invention can be applied to calligraphy and painting samples containing Bletilla striata juice paste with different aging degrees, and has wide practical value.

[0049] The aforementioned advantages stem from the synergy of two key technologies: first, the selective disruption of the hydrogen bond network of the paste layer by the borax-Bletilla striata polysaccharide complex; and second, the preferential adhesion and overall peeling of the swollen paste layer by the viscous transfer film. Both are indispensable—without borax pretreatment, the viscous transfer film struggles to overcome the strong cohesion of the intact BSP network; without the viscous transfer film, the complexed paste layer still lacks an effective directional transfer pathway. This synergistic mechanism enables this invention to form a complete solution in the field of mounting and peeling paste containing Bletilla striata juice, distinct from existing technologies. Attached Figure Description

[0050] Figure 1 This is a schematic flowchart of the method of the present invention;

[0051] Figure 2 This is a schematic diagram of the interfacial interaction between the viscous transfer film and the swollen paste layer in Example 1;

[0052] Figure 3 The images shown are scanning electron microscope (SEM) images (×50) of different samples in Example 3 of this invention. Detailed Implementation

[0053] The present invention will be further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein.

[0054] Example 1: Preparation and mounting of simulated calligraphy and painting samples made from Bletilla striata juice paste

[0055] (I) Preparation of simulated calligraphy and painting samples using Bletilla striata juice paste

[0056] Due to the scarcity of cultural relic samples, this embodiment uses self-prepared simulated cultural relic samples for experiments. Red Star brand raw Xuan paper (Anhui Jingxian Xuan Paper Factory, cotton-based single-layer Xuan paper, 0.10mm thick, basis weight 27g / m³) was selected. 2 The following materials were used as the painting core and the paper for the artwork: Bletilla striata tubers were pulverized and added to deionized water at a ratio of 1:10 (w / v). The mixture was extracted at 60°C for 2 hours, centrifuged, and the supernatant was collected to obtain a Bletilla striata polysaccharide extract (solid content approximately 2.5%). A paste was prepared using a BSP:wheat starch ratio of 1:5 (w / w), with a solid content of 8%, and gelatinized at 80°C for 30 minutes, then cooled to room temperature.

[0057] Apply the paste evenly to the back of the Xuan paper (painting core), with a coating amount of 0.15g / cm². 2 A second layer of Xuan paper (the base paper) was then applied, and the paper was rolled out with a soft brush to remove air bubbles. It was then allowed to air dry at room temperature (25±2℃, relative humidity 55±5%) for 72 hours. The prepared mounting was cut into 15cm×15cm pieces and placed in an aging test chamber for accelerated aging at 105±2℃ under dry heat for 72 hours, yielding a simulated sample of calligraphy and painting using Bletilla striata juice paste. According to research by Rasch et al., these conditions are approximately equivalent to aging under natural conditions for 18-25 years. After aging, the paper sample's pH value decreased to 5.8±0.3, tensile strength decreased by approximately 42%, and folding endurance decreased to 12±3 times. The degree of embrittlement was comparable to typical damaged Ming and Qing dynasty calligraphy and painting samples in the museum's collection.

[0058] (II) Steps for removing and restoring the mounting (e.g.) Figure 1 (As shown)

[0059] (a) Interface preprocessing

[0060] Preparation of the treatment solution: 2 wt% borax + 8 vol% glycerol + 0.2 mol / L urea, diluted to volume with deionized water. Borax hydrolyzes in water to form tetrahydroxyborate [B(OH)4]. - The ion forms a stable five-membered cyclic borate ester complex with the cis-ortho-dihydroxy group on the BSP molecular chain, thereby disrupting the hydrogen bond network of BSP and reducing the viscosity of the system.

[0061] Apply the treatment solution evenly to the back of the painting (approximately 0.3 mL / cm²). 2 The paste was covered with a polyethylene plastic film for 90 minutes to maintain moisture. During this time, borax ions penetrated into the paste layer and underwent a complexation reaction with the cis-hydroxyl groups of BSP. Urea, acting as a hydrogen bond competitor, further weakened the intermolecular forces. After treatment, the paste layer swelled significantly, increasing in thickness by approximately 40%, and its color changed from translucent to milky white, indicating that the complexation reaction had been fully carried out and the hydrogen bond network had been disrupted.

[0062] (b) Preparation of viscous transfer membrane

[0063] Formulated by weight ratio: sodium alginate 2%, gelatin 1%, glycerol 15%, deionized water 82%.

[0064] Preparation process:

[0065] (1) Gelatin was swollen in a 60°C water bath for 30 minutes;

[0066] (2) Add sodium alginate and glycerol, and stir at 60°C for 2 hours until completely dissolved;

[0067] (3) Vacuum degassing (-0.1MPa, 30 minutes);

[0068] (4) Cast onto a release film with a thickness of 1.5 mm, and immediately spray with 0.05 M CaCl2 solution for crosslinking for 30 seconds;

[0069] (5) After equilibration for 24 hours at 25℃ and 65% relative humidity, a gel film with a water content of 70% is formed.

[0070] The prepared viscous transfer membrane has a three-layer structure: the surface adhesion layer is a sodium alginate-rich region with high adhesion; the middle interpenetrating network layer is a sodium alginate / gelatin interpenetrating network (IPN) providing moderate cohesive strength; and the bottom support layer is a high cross-linking density support layer. Figure 2 The diagram shows the interface between the viscous transfer film and the swollen paste layer; the direction of the dashed arrows in the diagram indicates the path of adhesive force transmission.

[0071] (c) Viscous transfer operation

[0072] Remove the moisturizing film and blot away excess liquid on the back of the painting with filter paper. Cut the viscous transfer film to an appropriate size and attach it to the treatment area. Gently roll it from the center to the edge with a soft brush to remove air bubbles. Place the coated sample on a horizontal platform and cover it with a silicone pad (2-3 mm thick, Shore A hardness approximately 40A) and a rigid pressure plate (with the same area as the coated sample). Apply pressure at 3.0 g / cm³. 2 A counterweight was applied to the surface density of the coating, and the pressure was maintained for 45 minutes, during which the ambient temperature was kept at 25±1℃. During this period, the surface layer of the viscous transfer film and the swollen paste layer were in full contact, forming an adhesion interface through hydrogen bonds and van der Waals forces. Since the adhesion force of the viscous transfer film is greater than that of the paste layer and the painting paper (Adhesion / Cohesion ratio > 1.5), and the cohesion of the paste layer has been significantly reduced after borax treatment, the interfacial interaction is beneficial to the subsequent overall transfer.

[0073] (d) Controlled stripping

[0074] Slowly peel off the adhesive transfer film at a 20° angle, at a speed of approximately 50 mm / min. Observation revealed that the breakage during peeling occurred at the interface between the artwork and the paste. The paste layer adhered entirely to the surface of the transfer film, appearing as a uniform milky white film, with only a very thin transparent underlayer remaining on the back of the artwork. Repeat steps (b) and (c) twice until the paper can be separated without resistance.

[0075] (e) Post-processing

[0076] Gently wipe the back of the painting with a cotton swab moistened with deionized water to remove any trace residue. The original paper should be preserved intact and flattened for further research. After the painting dries, proceed with standard restoration procedures such as inking and brush rejoining.

[0077] Example 2: Formulation and Performance Verification of Adhesive Transfer Membrane

[0078] (I) Preparation of viscous transfer membrane:

[0079] Formulated by weight ratio: sodium alginate 2%, gelatin 1%, glycerol 15%, deionized water 82%.

[0080] Preparation process:

[0081] (1) Gelatin was swollen in a 60°C water bath for 30 minutes;

[0082] (2) Add sodium alginate and glycerol, and stir at 60°C for 2 hours until completely dissolved;

[0083] (3) Vacuum degassing (-0.1MPa, 30 minutes);

[0084] (4) Cast onto a release film with a thickness of 1.5 mm, and immediately spray with 0.05 M CaCl2 solution for crosslinking for 30 seconds;

[0085] (5) After equilibration for 24 hours at 25℃ and 65% relative humidity, a gel film with a water content of 70% is formed.

[0086] Three batches of viscous transfer membranes were prepared according to the above method, and their performance was tested. The results are shown in Table 1.

[0087] Table 1

[0088]

[0089] As shown in Table 1, the viscous transfer film prepared by this formulation has the following performance characteristics:

[0090] (1) The tackiness is 230±10min (about 3.8 hours), which meets the operating window requirement of 2-4 hours and ensures the adhesion stability of the membrane during the 45-minute pressure consolidation process;

[0091] (2) The paste residue rate was 5.5±0.5%, which is close to the control target of 5%, indicating that the membrane can completely transfer the vast majority of the paste layer to the membrane surface;

[0092] (3) The A / C ratio is 1.6-1.7, which is greater than the ideal threshold of 1.5, indicating that the adhesion of the film to the paste layer is significantly greater than its own cohesive strength. When peeling, the ideal interface destruction mode can be achieved, that is, the paste layer is transferred to the transfer film as a whole, while the surface of the painting core is clean and has no obvious residue.

[0093] (4) Excellent film-forming properties, uniform film appearance, soft and elastic, can be completely peeled off from the release film without brittleness or excessive adhesion.

[0094] (II) Verification of the necessity of viscous transfer membrane

[0095] To verify the necessity of the adhesive transfer film in the mounting process, a control group experiment was set up: after the paste sample containing Bletilla striata polysaccharide (i.e. the simulated sample in Example 1) was treated with borax pretreatment solution (2wt% borax + 0.2mol / L urea + 8vol% glycerol, moisturized for 90 minutes), the adhesive transfer film was not attached, and the paper was directly peeled off at a 20° angle and a speed of 50mm / min.

[0096] Control group results: The adhesive between the backing paper and the painting core was strong and could not be separated by hand. Observation revealed that the painting core and backing paper remained tightly bonded at the glue layer. The separation interface occurred in half a layer of the painting core paper or half a layer of the backing paper (i.e., the paper fiber layer broke), rather than inside the glue layer or at the glue-paper interface. This is because borax complexation only weakened the hydrogen bond network of Bletilla striata polysaccharide, reducing the cohesive force of the glue layer from its intact state. However, the wetted paper fibers, in their swollen state, still maintained a strong interfacial adhesion to the glue layer. Chemical weakening alone was insufficient to achieve complete detachment of the glue layer.

[0097] Experimental results: After the same borax pretreatment, an adhesive transfer film was attached and pressure-bonded according to the method of this invention (weight loading surface density 3.0 g / cm³). 2 (Hold for 45 minutes), then slowly peel off the transfer film at a 20° angle and a speed of 50 mm / min. During the peeling process, the fracture surface is located at the interface between the painting core and the glue layer. The glue layer is completely adhered to the surface of the transfer film as a uniform milky white film. The fibers on the back of the painting core are loosely arranged, the surface is clean, and there is no obvious glue residue. The damage mode is the ideal interface damage.

[0098] The above comparative results show that although borax complexation pretreatment can reduce the cohesive force of the paste layer, it must be combined with an viscous transfer film to achieve overall directional transfer of the paste layer by utilizing the preferential adhesion of the transfer film to the swollen paste layer. Using chemical pretreatment alone without the physical transfer effect of the viscous transfer film cannot achieve non-destructive mounting and unmounting. This result verifies the necessity of the "chemical weakening + physical transfer" synergistic mechanism of this invention.

[0099] Example 3: Validation of the system specificity of Bletilla striata polysaccharide

[0100] To verify the effectiveness of the method of the present invention on paste containing Bletilla striata juice, two sets of comparative samples were prepared:

[0101] Group A (pure starch paste control): solid content 8%, gelatinized at 80℃ for 30 minutes, coating amount 0.15g / cm². 2 The composite paper was naturally dried at room temperature (25±2℃, relative humidity 55±5%) for 72 hours, and then placed in an aging test chamber for accelerated aging under dry heat conditions of 105±2℃ for 72 hours.

[0102] Group B (Bletilla striata-starch composite paste): Prepared according to the method in Example 1, BSP:wheat starch = 1:5, coating amount 0.15g / cm² 2 The composite paper was naturally dried at room temperature (25±2℃, relative humidity 55±5%) for 72 hours, and then placed in an aging test chamber for accelerated aging under dry heat conditions of 105±2℃ for 72 hours.

[0103] Both groups of samples were treated using the complete process of this invention: 2wt% borax + 8vol% glycerol + 0.2mol / L urea, moistened for 90 minutes; the viscous transfer membrane of Example 2 (2% sodium alginate, 1% gelatin, 15% glycerol) was used at 3.0 g / cm³. 2 Apply counterweights to the loaded surface density and hold for 45 minutes, then slowly peel at a 20° angle.

[0104] Figure 3 The SEM morphology comparison of Group A (pure starch paste) and Group B (Bletilla striata-starch composite paste) before and after being peeled off using the method of this invention is shown. Figure 3 As shown in (a), before uncoating, the fibers in group A were tightly wrapped in starch paste, and the spaces between the fibers were filled with amorphous material. After treatment by the method of this invention ( Figure 3 (b) In Group A, a large amount of paste residue was still visible on the back of the painting core, with discontinuous granular material between the fibers. Some fiber surfaces were rough and had microcracks, indicating that borax had a limited effect on weakening the complexation of pure starch paste, and that fiber damage occurred during the peeling process. Figure 3 As shown in (c), before uncoating, the fibers in group B were coated with Bletilla striata-starch paste, and the paste layer was dense and uniform. After treatment by the method of this invention ( Figure 3 (d) The fibers on the back of the painting core in Group B are loosely arranged, the surface is smooth and clean, there is no obvious glue residue, the fiber shape is intact, and there are no crushed or broken marks.

[0105] The above comparison results directly prove that the borax pretreatment in the method of the present invention has a selective complexing effect on paste containing Bletilla striata polysaccharide, but has a limited effect on pure starch paste, which reflects the system specificity of the method of the present invention.

[0106] Example 4: Comparison of different mounting and unmounting methods

[0107] The simulated samples prepared in Example 1 were processed using different methods:

[0108] (1) Untreated sample: without using borax treatment solution, directly moisturize with deionized water + 8 vol% glycerol + 0.2 mol / L urea for 90 minutes; the remaining steps are the same as in Example 1, and the same formula adhesive transfer film is used for transfer and peeling.

[0109] (2) Traditional water soaking method: Spray 25℃ distilled water evenly on the back of the painting, cover it with a damp towel and soak for 2 hours. After soaking, use a bamboo screwdriver to try to separate the painting. If there is a lot of resistance, extend the soaking time.

[0110] (3) Method of the present invention: Treatment according to the method of Example 1: 2wt% borax + 8vol% glycerol + 0.2mol / L urea treatment solution, moisturized for 90 minutes; using the viscous transfer membrane prepared in Example 1 (2% sodium alginate, 1% gelatin, 15% glycerol), at 3.0g / cm 2 Apply counterweights to the loaded surface density and hold for 45 minutes, then slowly peel at a 20° angle.

[0111] The experimental results show that:

[0112] (1) The painting core and the backing paper of the untreated sample after soaking in water for 2 hours were still tightly bonded at the glue layer. The separation interface occurred in half of the painting core paper or half of the backing paper (i.e., the paper fiber layer was broken). The failure mode was still cohesive failure, indicating that the action of water alone could not effectively weaken the BSP network.

[0113] (2) The surface of the complete process sample of the present invention is smooth and clean, with no obvious glue residue, intact fiber morphology, no crushing or breakage marks, and the destruction mode is ideal interface destruction (basically complete transfer). The viscous transfer mechanism realizes the overall peeling of the glue layer.

[0114] The above comparative experiments show that:

[0115] (1) Necessity of the borax complexation step: Although the same viscous transfer film was used in the borax-free pretreatment group, the paste on the painting core and the backing paper was still tightly bonded. This directly proves that the complexation reaction of borax and Bletilla striata polysaccharide is the core step for reducing the cohesion of the paste layer and achieving efficient viscous transfer, and is indispensable.

[0116] (2) The role of the viscous transfer membrane: Even without borax pretreatment, the viscous transfer membrane can still achieve partial separation, indicating that its adhesive selectivity design has a certain effect; however, the viscous transfer membrane can only perform at its best after borax complexes and weakens the BSP network.

[0117] (3) Synergistic advantages of the present invention: After peeling off the film, the surface of the transfer film was found to be covered with a complete milky white paste layer. The fibers on the back of the painting core were loosely arranged, the surface was clean, and there was no obvious paste residue. This indicates that the fracture surface during the peeling process was located at the interface between the painting core and the paste layer, achieving an ideal interface destruction mode. The synergistic effect of borax complexation and viscous transfer was significantly better than that of the control groups, verifying the integrity and indivisibility of the technical solution.

[0118] The above embodiments of the present invention are merely illustrative examples and are not intended to limit the implementation of the invention. Those skilled in the art can make other variations and modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A method for mounting and unmounting calligraphy and paintings using Bletilla striata juice paste based on borax-Bletilla striata polysaccharide complexation and viscosity transfer, characterized in that... Includes the following steps: (a) Interface pretreatment: Taking Bletilla striata juice paste calligraphy and painting as the object, apply a pretreatment aqueous solution containing 1-3wt% borax, 0.1-0.3mol / L urea and 5-10vol% glycerol to the back of the painting core, and cover it with a film for moisturizing treatment; (b) Adhesive transfer: Remove the covering film and attach the adhesive transfer film to the treatment area; the adhesive transfer film is made of 1-3 wt% sodium alginate, 1-3 wt% gelatin, 5-15 wt% glycerol, and water, and is treated with calcium ion crosslinking. (c) Controlled peeling: at 2-4 g / cm 2 Apply counterweights to the loading surface density, peel off the viscous transfer film, and transfer the viscous material in the adhesive layer of the Bletilla striata juice paste painting to the viscous transfer film, thereby achieving the separation of the painting core and the backing paper in the Bletilla striata juice paste painting. (d) Interface cleaning: Check the interface, repeat steps (b) and (c) until the paper can be separated without resistance, and finally clean up any remaining impurities.

2. The method according to claim 1, characterized in that, In step (a), the molar ratio of urea to borax is 1:5 to 1:

15.

3. The method according to claim 1, characterized in that, In step (a), the moisturizing treatment takes 60-120 minutes.

4. The method according to claim 1, characterized in that, In step (a), the amount of the pretreatment aqueous solution used is 0.1-1 mL / cm³. 2 .

5. The method according to claim 1, characterized in that, In step (b), the method for preparing the viscous transfer membrane includes: (1) Soak the gelatin in a water bath; (2) Add sodium alginate and glycerol, and stir until completely dissolved; (3) Vacuum degassing; (4) Cast onto a release film and immediately spray with CaCl2 solution for crosslinking treatment; (5) Static equilibration treatment to form a gel-like viscous transfer membrane with a water content of 60-80wt%.

6. The method according to claim 5, characterized in that, In step (1), the temperature of the water bath is 50-70℃, and the swelling time is 20-40 minutes; In step (2), the stirring temperature is 50-70℃ and the stirring time is 1-3 hours.

7. The method according to claim 5, characterized in that, In step (3), the vacuum degassing pressure is -0.1 MPa and the time is 20-40 minutes; In step (4), the concentration of the CaCl2 solution is 0.05-0.2M, and the crosslinking time is 20-40 seconds; In step (5), the conditions for static equilibration are: 20-30℃, relative humidity 60-70%, and equilibration time 20-30 hours.

8. The method according to claim 1, characterized in that, In step (c), the counterweight is held for 30-60 minutes.

9. The method according to claim 1 or 8, characterized in that, In step (c), the viscous transfer film is peeled off at an angle of 10-30°.

10. The method according to claim 1, characterized in that, In step (d), the remaining impurities are finally cleaned with a moistened cotton swab.